2016
DOI: 10.1111/cdev.12632
|View full text |Cite
|
Sign up to set email alerts
|

Children's Sympathy, Guilt, and Moral Reasoning in Helping, Cooperation, and Sharing: A 6‐Year Longitudinal Study

Abstract: This study examined the role of sympathy, guilt, and moral reasoning in helping, cooperation, and sharing in a 6-year, three-wave longitudinal study involving 175 children (M 6.10, 9.18, and 12.18 years). Primary caregivers reported on children's helping and cooperation; sharing was assessed behaviorally. Child sympathy was assessed by self- and teacher reports, and self-attributed feelings of guilt-sadness and moral reasoning were assessed by children's responses to transgression vignettes. Sympathy predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
4
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 58 publications
5
55
4
8
Order By: Relevance
“…While the previous sections summarized dissociations between early forms of prosocial behavior, there are also a few studies -mostly with older preschool or school-aged children [20][21][22] -that reported some modest relations. Some of them used other-report measures of children's prosocial behavior that have disadvantages when assessing subtle differences in behavioral phenomena [23].…”
Section: Relations Between Different Forms Of Prosocial Behaviormentioning
confidence: 99%
“…While the previous sections summarized dissociations between early forms of prosocial behavior, there are also a few studies -mostly with older preschool or school-aged children [20][21][22] -that reported some modest relations. Some of them used other-report measures of children's prosocial behavior that have disadvantages when assessing subtle differences in behavioral phenomena [23].…”
Section: Relations Between Different Forms Of Prosocial Behaviormentioning
confidence: 99%
“…Thus, this motivational mechanism can support costly behavior, requiring self‐regulation. Notably, individuals are often able to reflect on their prosocial and moral values, and to explain why those values are correct and should take precedence over other considerations (e.g., self‐oriented concerns)—a capability known as moral reasoning; such awareness can strengthen the tendency to act in accordance with one's prosocial norms and values, even at a cost to the self (e.g., Eisenberg et al., ; Malti et al., , discussed below).…”
Section: Concern About Doing the Right Thing Vis‐à‐vis Othersmentioning
confidence: 99%
“…The role of such self‐reflective, anticipatory guilt was examined by Malti et al. (), together with two other motivational mechanisms discussed earlier: sympathy for others’ distress and moral reasoning reflecting internalized prosocial norms. The authors examined how these three distinct motivations predict three prosocial behaviors (helping, cooperating, and sharing) in a longitudinal study spanning ages 6–12.…”
Section: Concern About Doing the Right Thing Vis‐à‐vis Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…The PNS has been implicated in children's other‐oriented, social‐emotional capacities, such as sympathy and prosocial behaviors (Hastings & Miller, ; Malti et al, ). A theorized anatomical route for the PNS's involvement in prosociality is the nucleus ambiguus, which is the point of origin for the myelinated vagus nerve.…”
Section: Introductionmentioning
confidence: 99%